Assessment of the accuracy of different systems for measuring football velocity and spin rate in the field - Okholm Kryger, K.; Mitchell, S.; Forrester, S. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2019)
The aim of this study was to measure the level of agreement of four portable football velocity and spin rate measurement systems (Jugs speed radar gun, 2-D high-speed video, TrackMan and adidas miCoach football) against a Vicon motion analysis system. One skilled male university football player performed 70 shots covering a wide range of ball velocities (12-30 m s-1) and spin rates (94-743 r/min). A Bland-Altman analysis was used to assess the level of agreement. For ball velocity, the 2-D high-speed video had the smallest systematic error, followed by the radar gun, TrackMan and miCoach football at 0.2, 0.4, 0.5 and 4.8 m s-1, respectively. A similar ranking was also observed for the random errors (95% confidence intervals: ±0.4, ±1.5, ±1.9 and ±6.0 m s-1). The first three systems all tracked ball velocity in >90% of shots, while the miCoach football tracked slightly fewer shots (79%). For spin rate, the miCoach football had a much smaller systematic error (4 vs 38 r/min) and random error (95% confidence intervals: ±24 vs ±355 r/min) compared to TrackMan. The miCoach also successfully tracked spin rate in more shots than the TrackMan (79% vs 44%). These results indicate that 2-D high-speed video would be the preferred option for the field assessment of ball velocity; however, radar gun and TrackMan may also be appropriate. A minimum of 10 frames of 2-D high-speed video, captured close to the ball starting position, was demonstrated to be sufficient in providing a reliable measure of ball velocity. The miCoach ball is the preferred option for field assessment of ball spin rate.